Gold and silver nanoparticle effects on ammonia-oxidizing bacteria cultures under ammoxidation. (February 2015) - Luo, Zhuanxi; Chen, Zheng; Qiu, Zhaozheng; Li, Yancai; Laing, Gijs Du; Liu, Aifen; Yan, Changzhou
Highlights: Nano-silver significantly inhibited bacterial ammoxidation in the aquatic environment. The ammoxidation inhibition resulted from AOB biodiversity and abundance reduction. The AOB biodiversity and abundance and the ammoxidation were not inhibited by nano-gold. Nano-Ag would affect nitrogen cycling but nano-Au would not after entering aquatic environment. Abstract: Owing to their wide application in industry and manufacturing, understanding the environmental safety of gold (Au) and silver (Ag) nanoparticles entering aquatic environment is a global issue of concern. For this study, ammonia-oxidizing bacteria (AOB) enrichment cultures reproduced from surface sediments taken from the Jiulong River estuary wetlands (Fujian Province, China) were spiked with nano-Ag and nano-Au to determine their impact on ammoxidation and the mechanisms involved in the process. Results showed that nano-Ag significantly inhibited bacterial ammoxidation in aquatic environment, with the average ammoxidation rate decreasing with increasing nano-Ag concentration. The average ammoxidation rate was significantly correlated to the Shannon index, the Simpson index, and AOB abundance. This suggested that ammoxidation inhibition resulted primarily from AOB biodiversity and abundance reduction, caused by the antibacterial property of nano-Ag. However, AOB biodiversity and abundance as well as bacterial ammoxidation were not inhibited by nano-Au (with a maximum experimental concentration of 2 mg L −1 ). Moreover, an insignificant correlation was found between AOB biodiversity and abundance and the average ammoxidation rate under the nano-Au treatment. Given that ammoxidation is regarded as a rate-limiting procedure in nitrogen (N) circulation, nano-Ag would affect N cycling but nano-Au would not after entering aquatic environments. Identified nano-Ag and nano-Au impacts on ammonium nitrogen transformation could be generalized in aquatic environment according to their extensive representation in the phylogenetic tree.